Implementasi Moderasi Beragama dan Nilai Rahmatan lil-‘Alamin dalam Pendidikan Agama Islam pada Berbagai Jenjang Pendidikan - Arif Rahman Hakim; Isnan Rojibillah; Ilyas Rohili; Bambang Samsul Arifin; Uus Ruswandi (At Turots: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (IRE) holds a strategic role in shaping the moral character and identity of students within Indonesia’s diverse and multicultural society. In recent years, the challenges of growing intolerance, exclusivism, and radicalism have raised concerns about the younger generation’s ability to live harmoniously in a plural nation. These conditions require learning approaches that highlight balance, tolerance, inclusivity, and universal humanitarian values. Within this context, two important concepts religious moderation and the Islamic principle of rahmatan lil-‘alamin must be integrated into the design and practice of Islamic education. Religious moderation emphasizes adopting a middle path, rejecting extremism, and respecting differences, while rahmatan lil-‘alamin presents Islam as a mercy for all creation, transcending boundaries of culture, ethnicity, and belief. This study seeks to analyze how these values are implemented in IRE at the levels of elementary, secondary, and higher education. The research applies a literature review with a descriptive qualitative approach, examining previous studies, educational policies, and scholarly discourse. The findings reveal that at the elementary level, values are instilled through habituation of tolerance, empathy, and compassion; at the secondary level, through contextual religious understanding, critical discussion, and dialogue; and at the university level, through curriculum development, academic research, and community service activities that strengthen national awareness and global responsibility. In conclusion, IRE contributes significantly to forming a religious, moderate, and peace-oriented generation. Teachers and lecturers are key agents in nurturing inclusive Islamic values and promoting a culture of civility.